Engaging learning with game on food and nutrition for pre-school children / Cassandra Yen Pei Ying, Danakorn Nincarean Eh Phon and Mohd Faaizie Darmawan - Yen, Pei Ying (Cassandra); Eh Phon, Danakorn Nincarean; Mohd Faaizie, Darmawan (UiTM Press, 2020)
With the growing rates of children obesity and concerns on the related health consequences, the awareness in transforming children’s eating habits to a healthier direction to reduce their threat of developing diet-related disease during adulthood has been growing in recent years. Recent evidence suggests that a game-based approaches have a potential in health and wellbeing sector. This research is conducted based on two main aspects: development of game application on food and nutrition for pre-school children and evaluation involving users on the usability of the developed game. This game application has been developed based on the ADDIE model which consist of five phases, Analysis, Design, Develop, Implementation and Evaluation. The usability evaluation on the game application involved children in early ages. The genre of the games is based on platform and it is a single-player game that contains three modules: food pyramid, healthy maze, and my plate. For the usability, the game application received positive feedbacks from the users where they gain some knowledge and enjoy playing the game. This finding provides a valuable knowledge to the design and development of the game application in food and nutritions sector.